Analisis Pengaruh Tingkat Pengangguran Terbuka dan Rata-rata Lama Sekolah terhadap Tingkat Kemiskinan di Barlingmascakeb Periode 2015-2025 - Maulia Tantri Hidayah; Dian Isnawati; Aldila Krisnaresanti (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Economic development aims to improve well-being by reducing poverty, inequality, and unemployment. This study aims to test and analyze the partial and simultaneous effects of the Open Unemployment Rate (OUR) and Average Years of Schooling (AYS) on poverty rates in the Barlingmascakep region (Banjarnegara, Purbalingga, Banyumas, Cilacap, and Kebumen) for the period 2015–2025. Using a quantitative approach with multiple linear regression analysis, this study processed secondary time-series data from the Central Java Provincial Statistics Agency (BPS) using SPSS 27 software. The results indicate that all classical assumption tests were met. Simultaneously, through the F-test, TPT and RLS significantly influence poverty, where the calculated F (14.491) > table F (3.195) with an Adjusted R-Square value of 35.5%. Partially, through the t-test, the TPT variable (β = -1.131; p = 0.001) and RLS (β = -1.445; p = 0.036) have a negative and significant effect on the poverty rate. The negative impact of TPT indicates an anomaly in the labor market dominated by the informal sector and educated unemployed individuals from wealthy families, while the negative impact of RLS supports human capital theory, in which improvements in educational quality tangibly contribute to poverty reduction through increased individual productivity.